Interlanguage Pragmatic Study of Politeness in Requesting among English Education Students - Gina Nanda Utama; Jauhar Helmie; Halimah Halimah (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2025)
This study aims to uncover the politeness strategies which are used by English Education Students/Non Native Speakers of English (NNS) in requesting and compared it to the Native Speakers of English (NS). The main data was obtained from Discourse Completion Test (DCT) with six situations shared to 84 NNS and 6 NS of English as parameter. All six situations in the DCT are based on the sociolinguistics variables such as distance and imposition. The data from DCT are also supported by the data from interview and observation. All the data are classified and analysed by using the theory of politeness strategies from Brown and Levinson (1987), Yule (2000) and Cutting (2002). It revealed that both Native Speakers (NS) of English and Non Native Speaker (NNS) participants use interrogative form in expressing request, except in expressing bald on record strategy. In addition both NS and NNS participants in this study frequently use negative politeness strategy with more than 50% in each situation. Moreover in the situations which have far social distance, all of the NS participants use negative politeness strategy. In doing negative politeness strategy both NS and NNS participants tend to use modal such as “May I…” or “Would you ...” It is also strengthened by the NNS’ statements in interview that they were taught to use modal and interrogative forms in expressing request since Junior and Senior High School. In addition they also stated that they frequently watch western movies to improve their skills in using English for daily communication, such as requesting. Therefore, it also helps them to decrease any possibility to do pragmatic failure. However, NS participants tend to be more brief and straighter to the point in expressing request than the NNS participants especially in the situations which have low imposition level.